EFEKTIVITAS PELAKSANAAN KARTU KEPENDUDUKAN ELEKTRONIK PADA PELAYANAN KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN GROBOGAN TAHUN 2019 DALAM PENINGKATAN KUALITAS PELAYANAN PUBLIK - Nugroho, Cahyo Adhi; Yasminingrum, Yasminingrum; Winarni, Widiati Dwi (MAGISTRA Law Review, 2024)
This research is motivated by the fact that there are still problems related to the effectiveness of services provided by the Population and Civil Registration Service of Grobogan Regency, such as the uneven distribution of information regarding the preparation and completion of processing of population and civil registration documents, disorderly queues, discriminatory behavior in providing services to the community, and there are still a number of errors found in making eKTPs so that more time is needed to repair them. Things like this are often the obstacles encountered in the process of making e-KTPs at the Grobogan Regency Population and Civil Registration Service. This research aims to determine the effectiveness of services provided by the Grobogan Regency Population and Civil Registration Service. This research uses normative juridical methods. The data sources collected consist of primary data and secondary data. Data collection techniques through observation and interviews. Based on the results of the research, it shows that the effectiveness of the e-KTP making service at the Population and Civil Registration Service of Grobogan Regency uses the theory put forward by Soerjono Soekanto & Sri Mamudji, namely legal research carried out by examining library materials or secondary data as the basic material for research. conduct a search of regulations and literature related to the problem under study.